The Existence of Party Court in Completing the Internal Disputes of Political Parties in Indonesia (A Case Study of Persatuan Pembangunan Party) - S Suparto; A Admiral (Jurnal Dinamika Hukum, 2019)
Abstract According to Law Number 2 of 2011, “Any internal conflict inherent a political party, is resolved by that party’s internal organ known as the Internal Dispute Settlement Committee. But unfortunately, not all internal conflicts were ironed out, just as what happened to Persatuan Pembangunan Party. Based on the results of the current study, several factors could be identified to influence the resolution of internal political party disputes, including 1). the inability of the disputed internal party to pay heed to the decision of the Party Court. 2). the government violation of the decision made by the Party Court with biased interference. 3). There is doubtful neutrality considering the membership of the Party Court who comes from internal political parties. 4). Not considering the Party Court's decision while adjudicating disputes over the management of political parties.Keywords: Party Court, Decision, Final.